A diversified tetrapod ichnite fauna from the Lower Cretaceous Hekou Group of Gansu Province, China. (2nd November 2021) - Xing, Lida; Peng, Cuo; Lockley, Martin G.; Wang, Yongdong; Li, Daqing; Klein, Hendrik; Yang, Jingtao; Li, Longfeng; Persons, W. Scott; Wang, Miaoyan
ABSTRACT: Dinosaur and other tetrapod tracks are already known from multiple (~25) sites in the Early Cretaceous Hekou Group of Gansu Province. In addition to large sites (e.g. Yanguoxia) which have yielded more than 1500 tracks, small sites are important for verifying the distribution of morphotypes (ichnotaxa) over a wider region. Documentation of five newly-reported sites in the Honggu area supports previous studies which indicate a saurischian dominated (theropod and sauropod) ichnofauna with Asianopodus a common component of many assemblages. Ornithopod tracks also occur in several assemblages probably representing two morphotypes ( Caririchium and Ornithopodichnus ). One site reveals evidence of a small ornithopod progressing quadrupedally.